Distribution of phosphatase activity and various bacterial phyla in the rhizosphere of Hordeum vulgare L. depending on P availability. (October 2015) - Spohn, Marie; Treichel, Nicole Simone; Cormann, Michael; Schloter, Michael; Fischer, Doreen
Abstract: Despite the importance of the rhizosphere for nutrient turnover, little is known about the spatial patterns of organic phosphorus mineralization by plants and by microorganisms in the rhizosphere. Therefore, the distribution of acid and alkaline phosphatase activity and the abundance of bacteria belonging to various bacterial phyla were investigated in the rhizosphere of barley ( Hordeum vulgare L.) as dependent on the availability of inorganic P. For this purpose, we conducted a greenhouse experiment with barley growing in inclined boxes that can be opened to the bottom side (rhizoboxes), and applied soil zymography and fluorescence- in situ -hybridization (FISH). Acid phosphatase activity was strongly associated with the root and was highest at the root tips. Due to P fertilization, acid phosphatase activity decreased in the bulk soil, and less strongly in the rhizosphere. Alkaline phosphatase activity, i.e., microbial phosphatase activity was high throughout the soil in the control treatment and was reduced due to inorganic P fertilization especially in the rhizosphere and less strongly in the bulk soil. P-fertilization slightly increased the total number of bacteria in the rhizosphere. Moreover, P-fertilization decreased the abundance of Firmicutes and increased the abundances of Beta- and Gamma-Proteobacteria . The total number of bacterial cells was significantly higher at the root surface than at the root tip and at a distance of 30 μm from the root surface. Our results show that alkaline phosphatase activity decreased more strongly in the rhizosphere than in the bulk soil due to P fertilization, which might be because of greater C deficiency in the bulk soil compared to the rhizosphere. Furthermore, the results indicate a spatial separation between hotspots of acid phosphatase activity and hotspots of bacteria in the rhizosphere of H. vulgare . Taken together, our study shows that bacteria and phosphatase activity were very heterogeneously distributed in soil, and that the effects of P fertilization on phosphatase activity differed strongly between bulk soil and rhizosphere as well as between various zones of the rhizosphere. Highlights: The number of bacterial cells was higher at the root surface than at the root tip. Acid phosphatase activity was associated with the root, and was highest at the root tip. Alkaline, i.e., microbial phosphatase activity decreased due to P fertilization in the rhizosphere. Microbial phosphatase activity was likely not only controlled by P availability but also by C availability. The effect of P fertilization differed between the zones of the rhizosphere.